Prevalence study of Pseudomonas aeruginosa in Teaching Tikrit Hospital from different sources. - Manar. A. Kamal; Chatin I. Aldin; Ali. S. Husein (Tikrit Journal of Pure Science, 2023)
In the current study,it was isolated 117 samples from different sources ,the isolates were identification using bacteriological and biochemical tests,(bacteria swabs uptaked from wound, otitis media ,stool and urine and), ,out of 117 samples. only 18 specimens was positive for P.aeruginosa (14%) in the otitis media,(14%) in the stool,(3%) in the wound and (0%) in the urine.all bacterial isolates identified through the using of bacterial and biochemical test ,.P.aeruginosa isolates showed highy resistance to most used antibiotics especially Ceftriaxon (CRO), Erythromycin (E), Cefixime (CFM)100% followed by Cefepime (FEP), Carbenicillin (PY)44%, Tobramycin (TOB)22% and Piperacillin (PRL)16.66% but Norfloxacin (NOR) show the attractive activities against all P.aeruginosa isolates ,the resistance was 0%.